2016
DOI: 10.13075/mp.5893.00321
|View full text |Cite
|
Sign up to set email alerts
|

Ruminations as predictors of negative and positive effects of experienced traumatic events in medical rescue workers

Abstract: StreszczenieWstęp: Praca w służbach ratowniczych wiąże się z narażeniem na doświadczenia o charakterze traumatycznym. Celem badań było ustalenie roli procesów poznawczych, ściślej -różnych form ruminacji, jako predyktorów konsekwencji doświadczeń traumatycznych. Materiał i metody: Do udziału w badaniach zakwalifikowano 120 ratowników (80 mężczyzn, 40 kobiet), którzy w związku z pełnieniem obowiązków zawodowych potwierdzili wystąpienie w ostatnich 5 latach przynajmniej jednego zdarzenia traumatycznego. Wiek bad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
44
1
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(60 citation statements)
references
References 19 publications
6
44
1
9
Order By: Relevance
“…Post-traumatic growth does not mean that the experience of trauma is IJOMEH 2015;28(4) 709 experiencing the feeling of horror associated with war, and adults -civilians and soldiers involved in the war in Lebanon [32]. The positive relation between resiliency and post-traumatic growth is also confirmed by Polish research on a group of people who have lost someone close [36,37], in women after mastectomy [38], cardiological patients who experienced cardiological surgery [39], firefighters who have experienced traumatic events in the context of their work [12]. Resiliency can foster the occurrence of post-traumatic positive change directly but also indirectly, determining the choice of a more effective and adapted to the situation, ways of coping with a traumatic event, so one may assume that resiliency treated as personality feature will have an impact on PTG through the mediation of coping strategies.…”
Section: Introductionmentioning
confidence: 93%
“…Post-traumatic growth does not mean that the experience of trauma is IJOMEH 2015;28(4) 709 experiencing the feeling of horror associated with war, and adults -civilians and soldiers involved in the war in Lebanon [32]. The positive relation between resiliency and post-traumatic growth is also confirmed by Polish research on a group of people who have lost someone close [36,37], in women after mastectomy [38], cardiological patients who experienced cardiological surgery [39], firefighters who have experienced traumatic events in the context of their work [12]. Resiliency can foster the occurrence of post-traumatic positive change directly but also indirectly, determining the choice of a more effective and adapted to the situation, ways of coping with a traumatic event, so one may assume that resiliency treated as personality feature will have an impact on PTG through the mediation of coping strategies.…”
Section: Introductionmentioning
confidence: 93%
“…Medical personnel representatives—nurses, doctors, paramedics, that is people who have direct contact with patients and those who suffer because of their conditions or injured in accidents—are subject to negative consequences of exposure to trauma [ 8 13 ]. As underlined by Beck [ 14 ], STS is perceived as a professional risk factor among health care professionals.…”
Section: Introductionmentioning
confidence: 99%
“…Moderate STS symptoms were observed in 23.6% and 37.5% of participants showed low levels of STS symptoms. In studies in which Posttraumatic Checklist—PCL-5 was applied to evaluate STS symptoms [ 13 ] it was reported that among 5 professional groups (therapists, paramedics, nurses, social workers, and probation officers) the highest level of STS symptoms was presented by medical personnel and high probability of STSD occurrence was noted in 45.8% of paramedics and 40% of nurses employed in posttraumatic and palliative care wards.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…W badaniu psychologicznym zastosowano wywiad, MINI-MENTAL -Krótką Skalę Oceny Stanu Umysłowego (Mini-Mental State Examination -MMSE) [7], Zrewidowaną Skalę Wpływu Zdarzeń (Impact Event ScaleRevised -IES-R) Weissa i Marmara [8,9] zaadaptowaną do potrzeb badania (pytano o objawy w ostatnim miesiącu), Kwestionariusz Rozwoju Potraumatycznego (Post-Traumatic Growth Inventory -PTGI) Tedeschiego i Calhouna [10] oraz Kwestionariusz Ogólne-go Stanu Zdrowia w wersji 28-pytaniowej (General Health Questionnaire 28 item-scaled version -GHQ-28) Goldberga [11].…”
Section: Metodyunclassified